Menata Ulang Etika Ekonomi Islam di Luar Negeri: Konsep Zakat atas Penghasilan Profesi Menurut Yusuf al-Qaradawi dan Praktiknya di Kalangan Pekerja Migran Indonesia di Korea Selatan - Abdur Rokhim; Laila Afni Rambe; Ahmad Fauzan (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2025)
This study examines the legal status of zakat on professional income earned by Indonesian migrant workers in South Korea, based on the views of Yusuf al-Qaradawi. It evaluates the applicability of his perspective to the practice of zakat in this context. Using a descriptive-analytical approach, the research is based on field data obtained through observation and structured interviews. The findings show that professional income is subject to zakat if workers meet the legal and religious requirements. The income is classified as al-mal al-mustafad al-amalah, meaning earnings derived from wages or salaries through professional work. Furthermore, the average monthly income of these workers exceeds the nisab threshold when compared to the regional minimum wage, thus fulfilling the obligation for zakat. Yusuf al-Qaradawi’s interpretation remains relevant, as he draws an analogy between zakat on professional income and zakat on monetary assets, underscoring its necessity among migrant workers.